Stereotypy is strongly linked to multiple biomarkers of oxidative stress—A potential common etiology for Abnormal Repetitive Behaviors - Kendall M. Coden; Kaleigh J. Beacham; Beatriz E. Stix-Brunell; Roberta Moorhead; Kyna A. Byrd; Joanna N. Baker; Jerome T. Geronimo; Karen J. Parker; Joseph P. Garner (PLoS ONE, 2025)
Spontaneous stereotypies (abnormal, repetitive, and seemingly goal-less behaviors) in captive animals resemble stereotypies documented in patients with neurodevelopmental disorders, including evidence of homologous cortico-striatal dysfunction and shared behavioral abnormalities. While environmental risk factors for stereotypies are well documented, their developmental pathophysiology remains unclear. However, as previously found for compulsive behavior, there is growing evidence that REDOX imbalance may be linked to stereotypy. To examine the nature of this relationship, we first tested whether plasma glutathione level, the gold-standard biomarker of REDOX imbalance, is predictive of stereotypy severity in N = 19 C57BL/6 mice. After confirming the presence of this relationship, we used a proteomics approach (Olink) to identify a broader biomarker profile of dysfunction. We found expression of 9 proteins to correlate with plasma glutathione level, and expression of 15 proteins to correlate with stereotypy severity. A subset of these proteins additionally correlated with stereotypy severity in a validation cohort of CD1 mice (N = 28). Further supporting a role for REDOX imbalance in the developmental pathophysiology of stereotypies, the identified proteins were associated with REDOX physiology, dopamine physiology, and stereotypy-presenting human neurodevelopmental disorders. These data suggest REDOX imbalance may contribute to the developmental pathophysiology of Abnormal Repetitive Behaviors and highlight promising novel targets for intervention.